Isuzu and Nogwaja: A Strategic Partnership in Brand Identity - Willie, Michael Mncedisi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study explores the strategic partnership between Isuzu and adventurer Nogwaja, examining how it enhances Isuzu's brand identity while deepening consumer engagement through influencer marketing. Research Design and Methodology: This study utilized qualitative research methodology, incorporating a scoping literature review and case studies to examine the effectiveness of branding strategies in the automotive industry. It focused on Aaker's Brand Equity Model and the impact of partnerships, like Isuzu's collaboration with influencers, on brand perception and market appeal. Findings and Discussion: The partnership's success is attributed to authenticity, emotional engagement, and strategic communication. Nogwaja's alignment with Isuzu's values of adventure, resilience, and endurance strengthens the brand's credibility and fosters deeper consumer trust. Additionally, incorporating vernacular language and engaging on social media allows Isuzu to connect with local consumers and resonate with younger, adventure-driven audiences. Experiential marketing, exemplified by live events like the Mzansi Off-road Festival, further solidifies Isuzu's image as a high-performance, reliable brand. Implications: The study highlights the importance of authenticity, targeted engagement, and strategic brand positioning. It offers insights that can be applied across industries, particularly in leveraging influence partnerships and experiential marketing to enhance brand equity and long-term consumer loyalty. The Adventure-Brand Evolution Model developed from this study provides a framework for integrating emotional connection and cultural relevance in brand strategies.